Molecular detection of pox virus in Diyala province from pigeons - Basim Mohamed Manswr (Diyala Journal for Veterinary Sciences, 2024)
An infectious viral illness called pigeon chicken pox develops lesions that are fibro-necrotic, proliferating, or nodular in the feather-free parts of the skin or mucous membranes in the mouth, esophagus, and upper respiratory tract. The goal of this work was to search the Diyala pigeon for the pigeon pox virus (PPV) and its sequences molecularly. In this investigation, nodular lesions from Six pigeons from various Diyala locations that had the pox were gathered. For the purpose of PCR-based P4b gene identification, DNA materials were extracted. PCR was used to validate the virus detection, sequenced and BLST search was carried out and pairwise distance was inferred. And all of the field samples tested positive for PPV. Pigeon PPV was verified by PCR. Diyala birds have pigeon pox, and PCR should be used to diagnose the condition.